Demonstrating Compliance with Stringent Nitrogen Limits Using a Biological Nutrient Removal Process in California's Central Valley. (1st December 2015) - Merlo, Rion; Witzgall, Bob; Yu, William; Ohlinger, Kurt; Ramberg, Steve; De Las Casas, Carla; Henneman, Seppi; Parker, Denny
ABSTRACT: : The Sacramento Regional County Sanitation District (District) must be compliant with stringent nitrogen limits by 2021 that the existing treatment facilities cannot meet. An 11‐month pilot study was conducted to confirm that these limits could be met with an air activated sludge biological nutrient removal (BNR) process. The pilot BNR treated an average flow of 946 m 3 /d and demonstrated that it could reliably meet the ammonia limit, but that external carbon addition may be necessary to satisfy the nitrate limit. The BNR process performed well throughout the 11 months of operation with good settleability, minimal nocardioform content, and high quality secondary effluent. The BNR process was operated at a minimum pH of 6.4 with no noticeable impact to nitrification rates. Increased secondary sludge production was observed during rainfall events and is attributed to a change in wastewater influent characteristics.